Dissemination of drug abuse against youth in the sukoharjo area - Tri Harningsih; Muhammad Saiful Amin; Siwi Diyah Purwita Utami (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
NAPZA stands for Narcotics, Alcohol, Psychotropics and other Addictive Substances, including natural or synthetic substances which, when consumed, cause changes in physical and psychological functions, as well as lead to dependence. Counseling is carried out directly with initial introductions and followed by filling out pretests, presentation of material using power points about drug abuse against adolescents. Then continued the game session, filling out the questionnaire. The results of the analysis of the pretest and posttest values using SPSS with the Paired Sample T-test experienced a significant change with a significance value (2-tailed). The active participation of activity participants can be demonstrated with a 100% attendance rate. The results of the pre test and post test showed an increase by all participants. The success indicator of counseling is seen from the understanding of the entire material delivered by the extension worker.